Baltic Sea Coastal Eutrophication in a Thousand Year Perspective - Norbäck Ivarsson, Lena; Andrén, Thomas; Moros, Matthias; Andersen, Thorbjørn Joest; Lönn, Mikael; Andrén, Elinor (Frontiers in Environmental Science, 2019)
Sediment cores from three sites along the east-coast of Sweden, north-western Baltic Proper, have been studied with respect to lithologies, geochemistry and diatom assemblages to trace and date early human impact with emphasis on nutrient discharge. The three sites Bråviken, Himmerfjärden and Ådfjärden, have been impacted to various degree during the last millennia by multiple stressors like excessive nutrient discharge and hazardous substances, leading to coastal hypoxia, eutrophication and pollution. These stressors are mainly caused by drivers in the drainage area as increased human population, changed land use and point sources as industries and a sewage treatment plant. Even though their detailed history differs, the results show similar general patterns for all three sites. We find no evidence in our data from the coastal zone supporting the hypothesis that the extensive areal distribution of hypoxia in the open Baltic Sea during the Medieval Climate Anomaly was caused by human impact. Timing of the onset of man-made eutrophication, as identified from δ15N and changes in diatom composition, differs between the three sites, reflecting the site specific geography and local environmental histories of these areas. The onset of eutrophication dates to ~1800 CE in Bråviken and Himmerfjärden areas, and to ~1900 CE in the less urban area of Ådfjärden. We conclude that the recorded environmental changes during the last centuries are unique in a thousand year perspective.